Perancangan Sistem Informasi E-Bukom Media Komunikasi Orang Tua Dan Sekolah Berbasis Android ( Studi Kasus Ra Sepatan ) - Djamaludin, Djamaludin; Handayani, Fitriyani; Sofyan, Asep Abdul (Jurnal Ilmiah Fakultas Teknik, 2024)
Early Childhood Education (ECD) is a container cultivation and development of children's potential early on. ). But an institution can not do it alone the need for cooperation on the part of parents in monitoring the activities of children in school. As the development of globalization and development of information systems at this time parents can easily get the information needed. But the use of information technology has not been used as effectively as possible in RA Sepatan this in informing the school well as school activities and supervision of children's learning process is still manual use Bukom (Book Communication) media liaison parents and schools so that the information submitted is less accurate and effective, hence the need for a system that is digital and computerized. The research method applied in this research is the development of the waterfall method. Waterfall method is a model of systematic information system development and skuensial. The results of this study produced an android-based application program that can allow parents to obtain school information